2006
DOI: 10.1111/j.1399-0012.2006.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications after kidney transplantation: current epidemiology and associated risk factors

Abstract: This study suggests that the use of newer immunosuppressive agents in recent years is associated with some changes in the epidemiology of post-transplant infections. Enterococci have become the predominant uropathogen. Invasive fungal infections, although rare, are often fatal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
269
7
29

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(321 citation statements)
references
References 33 publications
16
269
7
29
Order By: Relevance
“…Comparatively, this result indicates that the incidence of infectious episodes in renal transplant recipients among us is equivalent to that observed in other countries of different regions in the world. In 2006, Alangaden et al 8 studied 127 renal transplanted patients at a North-American center and reported infectious complications in 51% of those recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, this result indicates that the incidence of infectious episodes in renal transplant recipients among us is equivalent to that observed in other countries of different regions in the world. In 2006, Alangaden et al 8 studied 127 renal transplanted patients at a North-American center and reported infectious complications in 51% of those recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Alangaden et al 8 reported a 7% incidence of infectious episodes in the surgical wound in a cohort of 127 renal transplanted patients. This result is also similar to that obtained in 2009 by a Spanish group reporting a 7.9% incidence of that same complication.…”
Section: Factors F O R the Development O F I N F E C T I O N After Trmentioning
confidence: 99%
“…Especially in the setting of renal transplantation, asymptomatic bacteriuria or symptomatic forms such as cystitis (Cys) and pyelonephritis (PN) account for approximately 47% of infectious complications (1) and up to 60% of bacteremias (2). The development of UTIs depends on anatomical factors, the integrity of host defense mechanisms, and the virulence of the infecting organisms (3).…”
mentioning
confidence: 99%
“…In this case, prophylaxis can be considered for a longer time, 20 since there is a description that the disease may occur later in those who are no longer using prophylactic medication. 21 It is important to note that although urinary infection is the most common in the renal transplant, 22 pulmonary infection is the main cause of sepsis and hospitalization in the ICU. 8,10,23,24 Traditionally, a greater number of infections are expected in the first 6 months of transplantation, a period in which immunosuppression is more intense.…”
Section: Discussionmentioning
confidence: 99%